ISLAMIC ECONOMY AS A PILLAR OF SUSTAINABLE FINANCIAL INCLUSION - Irwandi; Arifin, Asriadi (Proceeding International Conference on Islam and Civilization (ICONIC), 2026)
This study aims to analyze the role of Islamic economics as a pillar of sustainable financial inclusion through desk observation, reviewing various journals, official reports, and related literature. The results show that Islamic economic principles based on justice, balance, and welfare can be a humanistic solution in expanding financial access, especially for vulnerable communities who are not yet served by conventional systems. Islamic social instruments such as zakat, productive waqf, and qardhul hasan, as well as profit-sharing financing mechanisms, have proven to be fairer and have the potential to encourage economic empowerment. Furthermore, Islamic economics is closely related to the Sustainable Development Goals (SDGs) through the principle of maqasid al-shariah, which emphasizes shared welfare. By integrating ethical values ​​with economic practices, Islamic economics offers an inclusive framework that not only promotes financial access but also strengthens social cohesion and supports long-term development goals. Thus, Islamic economics can be an alternative paradigm for achieving inclusive and sustainable economic growth.